Biological responses in Musca domestica to fipronil and chlorfenapyr exposures - P. A. Shumilova; N. A. Sennikova; E. A. Silivanova; M. A. Levchenko (Regulatory Mechanisms in Biosystems, 2021)
Insect populations exist under acute and chronic exposures to lethal and sublethal insecticide concentrations. Among the sublethal effects of insecticides on insects are reductions in life span, development rates, population growth, fertility, fecundity, changes in sex ratio, deformities, changes in behaviour, feeding, searching, and oviposition. These effects may differ depending on the modes of action of insecticides, their doses, and developmental stage of application. This study evaluated the life-history parameters in Musca domestica Linnaeus, 1758 (Diptera:Muscidae) strains that were exposed to two insecticides (fipronil and chlorfenapyr) with different modes of action at sublethal concentrations in each generation up to tenth. Two approaches to each insecticide’s exposure were used in this study, particularly in one approach, only adults M. domestica were exposed to fipronil or chlorfenapyr and in another approach, only larvae were exposed to each insecticide. The susceptibility of adult flies to these insecticides was assessed by resistance ratio based on results of non-choice feeding bioassays. Fipronil exposure at the sublethal concentration in each generation did not affect the susceptibility of adult M. domestica (in the tenth generation) to fipronil. The resistance ratio values revealed tolerance to chlorfenapyr in adults of M. domestica strains that were exposed to this insecticide, independent of the approach used to insecticide exposure. Most of the life-history parameters (such as durations of separate developmental stages, the emergence duration, the adult emergence ratio, the female ratio, and the number of eggs per female per day) of the second, fourth, sixth, eighth, and tenth generations of the insecticide-exposed strains were similar to those of the control strain. At the same time, the sublethal effects of both insecticides fipronil and chlorfenapyr prolonged the larval duration (1.63–2.22 times) and the number of days from egg to adult (1.18–1.39 times) compared to the control strain. Further studies are needed to investigate a possible genetic variability in M. domestica in response to exposure of parental generation to sublethal doses of fipronil and chlorfenapyr.